Kinerja Keuangan Badan Usaha Milik Desa (Bumdes) Desa Kamoali Di Kabupaten Buton Selatan - Hesri Hesri; Jeni Susyanti; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The purpose of this study was to analyze the financial performance of village-owned enterprises (BUMDES) in Buton Selatan district.  The research method used in this research is descriptive qualitative analysis using data in the form of financial data from Bumdes. The data analysis method used is the liquidity ratio, profitability ratio, solvency ratio and activity ratio.  The results showed that the average Curent Ratio of Bumdes in Kamoali Village, South Buton Regency, was 198.6% (good), the average Net Profit Margin was 31.8% (very good), the average Return on Equity was 17.76% (good) on average.  the average Total Assets Turnover is 0.496 times (poor), and the average Debt to Equity Ratio is 5.54% (very good). Keyword: Management, financial performance, BUMDes